2008
DOI: 10.1192/bjp.bp.107.036707
|View full text |Cite
|
Sign up to set email alerts
|

Public health significance of mixed anxiety and depression: beyond current classification

Abstract: The data support the pathological significance of MADD in its negative impact upon population health. Dimensional approaches to classification may provide a more parsimonious description of anxiety and depressive disorders compared with categorical approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
134
0
7

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(150 citation statements)
references
References 20 publications
9
134
0
7
Order By: Relevance
“…Here, we will elaborate on the prevalence of MAD. Some researchers found MAD to be a highly prevalent condition (Das-Munshi et al, 2008;Schmidt et al, 2007;Zinbarg et al, 1994), whereas others reported marginal prevalence rates (Means-Christensen et al, 2006;Spijker et al, 2010;Weisberg et al, 2005). For example, we found an annual prevalence rate of .6% in the general population by administering the Composite International Diagnostic Interview and by applying criteria almost similar to the research criteria of DSM-IV, thus excluding those with a current anxiety disorder or depressive disorder as well as excluding those with a history of a major depressive disorder, dysthymic disorder, panic disorder, or generalized anxiety disorder (Spijker et al, 2010).…”
Section: Divergent Results Of Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we will elaborate on the prevalence of MAD. Some researchers found MAD to be a highly prevalent condition (Das-Munshi et al, 2008;Schmidt et al, 2007;Zinbarg et al, 1994), whereas others reported marginal prevalence rates (Means-Christensen et al, 2006;Spijker et al, 2010;Weisberg et al, 2005). For example, we found an annual prevalence rate of .6% in the general population by administering the Composite International Diagnostic Interview and by applying criteria almost similar to the research criteria of DSM-IV, thus excluding those with a current anxiety disorder or depressive disorder as well as excluding those with a history of a major depressive disorder, dysthymic disorder, panic disorder, or generalized anxiety disorder (Spijker et al, 2010).…”
Section: Divergent Results Of Previous Researchmentioning
confidence: 99%
“…Co-occurring subthreshold depression and subthreshold anxiety are associated with impaired functioning (Das-Munshi et al, 2008;Preisig et al, 2001;Roy-Byrne et al, 1994). For example, one fifth of work loss days occurred in those with co-occurring subthreshold depression and subthreshold anxiety (Das-Munshi et al, 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They are estimated to cause 1 in 5 days lost from work in Britain. 2 There are problems with access to care and with identification of people with CMHDs. In the 2007 household survey of adult psychiatric morbidity only 38% of people with CMHDs had asked their GP for help, and only 24% were receiving treatment (14% medication; 5% counselling; and 5% both).…”
Section: Introductionmentioning
confidence: 99%
“…En la presente investigación se encontró que las personas con ansiedad tenían un nivel de AP similar al de las personas sin trastornos, lo cual podría deberse a que el alto AP no necesariamente es indicador de bienestar (Cuadra & En este sentido, se debe mencionar la relevancia clínica y social que tiene el trastorno mixto de ansiedad depresión (Munshi, Goldberg, Bebbington, Bhugra & Brugha, 2008). La comorbilidad de los trastornos ansiosos y depresivos es muy elevada, y ha sido relacionada con variables como la cronicidad y la gravedad de los trastornos, los resultados del tratamiento y las recaídas, la búsqueda de tratamiento, el riesgo de suicidio y el funcionamiento general de los pacientes (Bair, et ál., 2013).…”
Section: Discussionunclassified